Anti-H1 histone antibodies in systemic lupus erythematosus: epitope localization after immunoblotting of chymotrypsin-digested H1. - Costa, O (1986)
Using micro enzyme-linked immunosorbent assay (micro-ELISA) anti-H1 antibodies are most frequently seen in systemic lupus erythematosus (SLE) (61.4% of patients). Positive anti-H1 ELISA reactions are rare in rheumatoid arthritis (RA) (5.8% of cases), melanomas (16.7%), leukaemias (13.6%) and other cancers (5.6%). In SLE, the immunoglobulins (Ig) which constitute anti-H1 antibodies are, by order of importance, IgM, IgG and IgA. By means of immunoblotting using H1 solutions digested by alpha-1-chymotrypsin fixed on collagen membranes, we have shown that all the SLE sera containing anti-H1 antibodies recognize the sequential epitopes that are found on the carboxy terminal tail and, for 28% of anti-H1 sera, also the epitopes present on the aminoterminal half. The technique used did not make it possible to determine with certainty whether anti-H1 autoantibodies are also directed against the conformational epitopes of the globular part of the molecule.